2020
DOI: 10.1101/2020.06.19.161901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oscillatory correlates of auditory working memory examined with human electrocorticography

Abstract: This work examines how sounds are held in auditory working memory (AWM) in humans by examining oscillatory local field potentials (LFPs) in candidate brain regions. Previous fMRI studies by our group demonstrated blood oxygenation level-dependent (BOLD) response increases during maintenance in auditory cortex, inferior frontal cortex and the hippocampus using a paradigm with a delay period greater than 10s. The relationship between such BOLD changes and ensemble activity in different frequency bands is complex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…However, these did not require an active task, which the visual literature suggests may be necessary; further work is needed. However, supporting a role of the hippocampus in pattern analysis, auditory working memory for tone frequency engages the hippocampus (Kumar et al, 2016(Kumar et al, , 2020 and correlates with speech-in-noise ability (Lad et al, 2020). Phonological working memory also correlates with speech-in-noise ability (Akeroyd, 2008), although there has been debate about this (F€ ullgrabe and Rosen, 2016).…”
Section: Ll Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these did not require an active task, which the visual literature suggests may be necessary; further work is needed. However, supporting a role of the hippocampus in pattern analysis, auditory working memory for tone frequency engages the hippocampus (Kumar et al, 2016(Kumar et al, , 2020 and correlates with speech-in-noise ability (Lad et al, 2020). Phonological working memory also correlates with speech-in-noise ability (Akeroyd, 2008), although there has been debate about this (F€ ullgrabe and Rosen, 2016).…”
Section: Ll Open Accessmentioning
confidence: 99%
“…The human hippocampus is also involved in working memory processes that are required for the analysis of acoustic patterns that evolve over time. Functional imaging (Kumar et al, 2016) has demonstrated increased blood-oxygen-level-dependent (BOLD) activity in the hippocampus when subjects hold tones in mind, and human local field potential recordings (Kumar et al, 2020) have demonstrated low-frequency oscillatory activity during the same process. Representations of auditory content are also available to the hippocampus during active listening.…”
Section: Mechanism 4: Interaction Between Brain Activity Related To Auditory Cognition and Dementia Pathologymentioning
confidence: 99%
“…Comparable findings linking unit activity to oscillatory phase or particular timepoints are yet to be reported for auditory memoranda, however the degree of synchrony among groups of neurons in rat CA1 can distinguish a tone frequency held in memory from another, even when such information is not carried in the firing rate of individual neurons (Takahashi and Sakurai, 2009). In humans, increases in hippocampal BOLD activity (Kumar et al, 2016) and low frequency oscillatory power (Kumar et al, 2021) emerge when human subjects keep a tone frequency in mind for comparison to a probe. It has been argued that the hippocampus is involved in retention over a few seconds only when the stimuli require complex highresolution binding (Yonelinas, 2013) or additional demands are placed on working memory (Jeneson and Squire, 2011), but neither were the case in the Kumar et al (2021) study.…”
Section: Time and Working Memory For Soundmentioning
confidence: 91%
“…In humans, increases in hippocampal BOLD activity (Kumar et al, 2016) and low frequency oscillatory power (Kumar et al, 2021) emerge when human subjects keep a tone frequency in mind for comparison to a probe. It has been argued that the hippocampus is involved in retention over a few seconds only when the stimuli require complex highresolution binding (Yonelinas, 2013) or additional demands are placed on working memory (Jeneson and Squire, 2011), but neither were the case in the Kumar et al (2021) study.…”
Section: Time and Working Memory For Soundmentioning
confidence: 99%
“…Recent years have shown an increasing interest in human ASTM (Arnott et al, 2005;Buchsbaum et al, 2005;Cappotto et al, 2021;Kumar et al, 2016;Lim et al, 2022;Noyce et al, 2022;Papagno et al, 2017), particularly in the context of electrophysiological oscillatory correlates (Kaiser, 2015;Kumar et al, 2021;Weisz et al, 2020;Wilsch & Obleser, 2016). Although previous work has predominantly focused on contrasting low-and high-load ASTM tasks, here, we ask what patterns of brain activity distinguish successful versus unsuccessful ASTM performance while the task, and stimuli presented to participants, remain fixed.…”
Section: Introductionmentioning
confidence: 99%